Comparative Analysis of Femoral Macro- and Micromorphology in Males and Females With and Without Hyperostosis Frontalis Interna: A Cross-Sectional Cadaveric Study - Cvetković, Danica; Jadžić, Jelena; Milovanović, Petar; Djonić, Danijela; Djurić, Marija; Ivović, Miomira; Nikolić, Slobodan; Živković, Vladimir (Calcified tissue international, 2020)
We hypothesized that subjects with hyperostosis frontalis interna (HFI), which represents local, endocranial thickening of the frontal bone, would express extra-calvarial manifestations of this condition. Therefore, we compared femoral bone mineral density, geometry, and microarchitecture of males and females with HFI to those without this condition as well as between males and females with HFI. The sample was taken from human donor cadavers, 38 males (19 with and 19 without HFI) and 34 females (17 with and 17 without HFI) that were age-matched within the same sex. The specimens of femoral bones were scanned using microcomputed tomography and dual-energy X-ray absorptiometry (DXA). Parameters of hip structure analysis (HSA) were calculated from data derived from DXA scans. Females with HFI had increased cortical bone volume fraction and their cortical bone was less porous compared to females without HFI. Males with HFI showed microarchitectural differences only with the trabecular bone. They had increased bone volume fraction and decreased trabecular separation compared to males without HFI, although with borderline significance. These microarchitectural changes did not have significant impact on femoral geometry and bone mineral density. The same, still unknown etiological factor behind HFI might be inducing changes at the level of bone microarchitecture at a remote skeletal site (femoral bone), in both sexes. These alterations still do not have the magnitude to induce obvious, straightforward overall increase of bone mineral density measured by DXA. HFI could be a systemic phenomenon that affects both males and females in a similar manner.